Predictors and prognosis of right ventricular function in pulmonary hypertension due to heart failure with reduced ejection fraction. (2nd May 2021) - Schmeißer, Alexander; Rauwolf, Thomas; Groscheck, Thomas; Fischbach, Katharina; Kropf, Siegfried; Luani, Blerim; Tanev, Ivan; Hansen, Michael; Meißler, Saskia; Schäfer, Kerstin; Steendijk, Paul; Braun‐Dullaeus, Ruediger C.
Abstract: Aims: Failure of right ventricular (RV) function worsens outcome in pulmonary hypertension (PH). The adaptation of RV contractility to afterload, the RV‐pulmonary artery (PA) coupling, is defined by the ratio of RV end‐systolic to PA elastances (Ees/Ea). Using pressure–volume loop (PV‐L) technique we aimed to identify an Ees/Ea cut‐off predictive for overall survival and to assess hemodynamic and morphologic conditions for adapted RV function in secondary PH due to heart failure with reduced ejection fraction (HFREF). Methods and results: This post hoc analysis is based on 112 patients of the prospective Magdeburger Resynchronization Responder Trial. All patients underwent right and left heart echocardiography and a baseline PV‐L and RV catheter measurement. A subgroup of patients ( n  = 50) without a pre‐implanted cardiac device underwent magnetic resonance imaging at baseline. The analysis revealed that 0.68 is an optimal Ees/Ea cut‐off (area under the curve: 0.697, P  < 0.001) predictive for overall survival (median follow up = 4.7 years, Ees/Ea ≥ 0.68 vs. <0.68, log‐rank 8.9, P  = 0.003). In patients with PH ( n  = 76, 68%) multivariate Cox regression demonstrated the independent prognostic value of RV‐Ees/Ea in PH patients (hazard ratio 0.2, P  < 0.038). Patients without PH ( n  = 36, 32%) and those with PH but RV‐Ees/Ea ≥ 0.68 showed comparable RV‐Ees/Ea ratios (0.88 vs. 0.9, P  = 0.39), RV size/function, and survival. In contrast, secondary PH with RV‐PA coupling ratio Ees/Ea < 0.68 corresponded extremely close to cut‐off values that define RV dilatation/remodelling (RV end‐diastolic volume >160 mL, RV‐mass/volume‐ratio ≤0.37 g/mL) and dysfunction (right ventricular ejection fraction <38%, tricuspid annular plane systolic excursion <16 mm, fractional area change <42%, and stroke‐volume/end‐systolic volume ratio <0.59) and is associated with a dramatically increased short and medium‐term all‐cause mortality. Independent predictors of prognostically unfavourable RV‐PA coupling (Ees/Ea < 0.68) in secondary PH were a pre‐existent dilated RV [end‐diastolic volume >171 mL, odds ratio (OR) 0.96, P  = 0.021], high pulsatile load (PA compliance <2.3 mL/mmHg, OR 8.6, P  = 0.003), and advanced systolic left heart failure (left ventricular ejection fraction <30%, OR 1.23, P  = 0.028). Conclusions: The RV‐PA coupling ratio Ees/Ea predicts overall survival in PH due to HFREF and is mainly affected by pulsatile load, RV remodelling, and left ventricular dysfunction. Prognostically favourable coupling (RV‐Ees/Ea ≥ 0.68) in PH was associated with preserved RV size/function and mid‐term survival, comparable with HFREF without PH.